Sek. Men. Keb. Ismail Petra (SMIP) hostel fee payment system / Shazwani Fathine Ab Rahim - Ab Rahim, Shazwani Fathine (2012)
As computer revolve and become faster and easier to use besides of easy to learn with so many sources, the student information management that previously perform manually can now be performed with the use of computers more effectively and efficiently than before. Originally, the hostel fee payments are record in manual files and then the receipts will be given to the student to be kept. This manual system however has occurs some problems where the manual files might easy damage and the files are highly risk if uncertain disaster happen especially in the monsoon season. Besides, it also quite hard to manage outdated student details and their fee payment records and as human being, the staff may also unrealized the errors occur in fee payment records that finally will faced some difficulties in producing accurate reports. Therefore this research is done to study the characteristics of web-based system besides to design and develop prototype of hostel fee payment management web-based system and finally to evaluate the usability of proposed system. The implementation of Waterfall model in this research is very helpful and suitable for management control. The evaluation of the system is done by distribute a set of questionnaire in order to produce some results. From the evaluation, it shows that the system 60% help the staff solve the problems and improve their performance. The revolution of technology may create more powerful system in the future. The SMIP Hostel Fee Payment System can soon be upgrade into online fee payment system as well as increases the accessibility of the user. Last but not least, it also recommend to improve the ability of the system by centralized the hostel fee payment management system with the school treasurer department system so that the system will be more effective and well-organized.